Use of the ICT by the academic community in a public university, Costa Rica (Educación y Tecnología, 2021)
The objective of this study is to analyze the use of Information and Communication Technologies (ICT) by the academic staff of a public university in Costa Rica. In this project, a simple random sampling was carried out in order to obtain a sample of 182 officials (N = 1134) from different academic units of the institution's headquarters. Instruments and materials: an ICT use questionnaire was prepared with 21 questions. Statistical analysis: a descriptive analysis was carried out in each question, by different services synthesized in these, such as through a general index of use of ICT (IGATIC) to determine if there is a relationship between the IGATIC with the labor condition, the area of knowledge and age using a t-Student test for the difference of means and two Kruskal-Wallis tests, one for each factor. The analysis of the information was carried out using the statistical software R, version 3.3.5. Results: regardless of gender, age or area of ​​knowledge, the academic population makes moderate use of ICT. It is possible to see a low use of bibliographic managers. Another result is that most of the people surveyed use Open Access databases and few use paid databases. Another piece of information is that the perception of academic staff regarding the Internet connection provided by the institution ranges from good to excellent. It is concluded that academic staff prefer to use office tools, either to create, edit or store documents.
Keywords: technological devices; technological tools; academic staff, Information and Communication Technology (ICT)